Surgical management of pediatric renin-mediated hypertension secondary to renal artery occlusive disease and abdominal aortic coarctation - Coleman, Dawn M; Eliason, Jonathan L; Beaulieu, Robert; Jackson, Tatum; Karmakar, Monita; Kershaw, David B; Modi, Zubin J; Ganesh, Santhi K; Khaja, Minhaj S; Williams, David; Stanley, James C (Journal of vascular surgery, 2020)
Renovascular hypertension (RVH) associated with renal artery and abdominal aortic narrowings is the third most common cause of pediatric hypertension. Untreated children may experience major cardiopulmonary complications, stroke, renal failure, and death. The impetus of this study was to describe the increasingly complex surgical practice for such patients with an emphasis on anatomic phenotype and contemporary outcomes after surgical management as a means of identifying those factors responsible for persistent or recurrent hypertension necessitating reoperation. A retrospective analysis was performed of consecutive pediatric patients with RVH undergoing open surgical procedures at the University of Michigan from 1991 to 2017. Anatomic phenotype and patient risk factors were analyzed to predict outcomes of blood pressure control and the need for secondary operations using ordered and binomial logistic multinomial regression models, respectively. There were 169 children (76 girls, 93 boys) who underwent primary index operations at a median age of 8.3 years; 31 children (18%) had neurofibromatosis type 1, 76 (45%) had abdominal aortic coarctations, and 28 (17%) had a single functioning kidney. Before treatment at the University of Michigan, 51 children experienced failed previous open operations (15) or endovascular interventions (36) for RVH at other institutions. Primary surgical interventions (342) included main renal artery (136) and segmental renal artery (10) aortic reimplantation, renal artery bypass (55), segmental renal artery embolization (10), renal artery patch angioplasty (8), resection with reanastomosis (4), and partial or total nephrectomy (25). Non-renal artery procedures included patch aortoplasty (32), aortoaortic bypass (32), and splanchnic arterial revascularization (30). Nine patients required reoperation in the early postoperative period. During a mean follow-up of 49 months, secondary interventions were required in 35 children (21%), including both open surgical (37) and endovascular (14) interventions. Remedial intervention to preserve primary renal artery patency or a nephrectomy if such was impossible was required in 22 children (13%). The remaining secondary procedures were performed to treat previously untreated disease that became clinically evident during follow-up. Age at operation and abdominal aortic coarctation were independent predictors for reoperation. The overall experience revealed hypertension to be cured in 74 children (44%), improved in 78 (46%), and unchanged in 17 (10%). Children undergoing remedial operations were less likely (33%) to be cured of hypertension. There was no perioperative death or renal insufficiency requiring dialysis after either primary or secondary interventions. Contemporary surgical treatment of pediatric RVH provides a sustainable overall benefit to 90% of children. Interventions in the very young (<3 years) and concurrent abdominal aortic coarctation increase the likelihood of reoperation. Patients undergoing remedial surgery after earlier operative failures are less likely to be cured of hypertension. Judicious postoperative surveillance is imperative in children surgically treated for RVH.